ENERGY SYSTEM DESIGN IN PACITAN REGENCY-EAST JAVA PROVINCE - Syam Widiyanto; Etika Nur'Aini; Dony Anggit Sasmito (Master in Systems Engineering, 2021)
Planning the construction of renewable energy plants in Pacitan district addresses the increasing electricity needs every year. Pacitan Regency is located on the coast with natural conditions in most of the mountains; there is a lot of renewable energy potentials such as water, wind and sunlight. Based on data from the central statistics agency of Pacitan district with the population increased by 0.18%/year. The energy system planning in this study allocates 70% of renewable energy generation and 30% of fossil plants by 2030.Projected availability of steam power plants with installed capacity of 2 x 315 MW, power capable of 560 MW. The distribution of renewable energy power plants is spread in the Pacitan area with hydroelectric power plants with a total target of at least 412 MW by 2025 and Pump Storage power plants with a total target of at least 1000 MW by 2025. Solar power plants have the potential of intensity radiation 4300 Wh/m2; the average air temperature is 32.5 0C and Solar Radiation 38.71%. Electricity generation waste power with a total target capacity of at least 84 MW. Wind potential with an average speed of 9 m/s. By 2030, the population of Pacitan district will reach 566,413 people, with an energy consumption of 843.85 kWh/capita; the demand required is 187,613 Mwh. By reducing the use of power plants from 100% to 30% can reduce CO^2 emissions to 125,419,390,667 Tons.